2000
DOI: 10.1074/jbc.275.14.10498
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Whereby Proliferating Cell Nuclear Antigen Stimulates Flap Endonuclease 1

Abstract: Flap endonuclease 1 (FEN1)1 is a member of the RAD2 superfamily of nucleases that play a critical role in DNA replication and repair in prokaryotes and eukaryotes (1-5). Both biochemical and genetic studies support a role for FEN1 during these cellular processes. Reconstitution reactions in vitro with either calf or human FEN1 illustrate the need for this nuclease during Okazaki fragment processing (6, 7) and long patch base excision repair (8). In Saccharomyces cerevisiae, a null mutant of the FEN1 homolog (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
178
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(200 citation statements)
references
References 45 publications
21
178
1
Order By: Relevance
“…Numerous studies indicate that a free 5Ј-end is required before FEN-1 can recognize and cleave at the base of the flap, and if the 5Ј-end of the flap is blocked, FEN-1 activity is inhibited (48,54). Taking these studies into account, Liu et al (52) proposed a model by which FEN-1 removes triplet repeats by a unique tracking mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicate that a free 5Ј-end is required before FEN-1 can recognize and cleave at the base of the flap, and if the 5Ј-end of the flap is blocked, FEN-1 activity is inhibited (48,54). Taking these studies into account, Liu et al (52) proposed a model by which FEN-1 removes triplet repeats by a unique tracking mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus EXO-1 cleaves primarily at the base of the flap, yielding a nicked duplex intermediate that can be readily sealed by ligase. In contrast, FEN-1 (in the absence or presence of WRN) incises primarily 1 nt into the downstream annealed region, and to a lesser extent at the base of the flap, resulting in primarily a 1-nt gap duplex and a lower amount of nicked duplex, respectively (24,41). This difference may be important during Okazaki fragment processing of double flap substrates in which the upstream primer has a single unannealed nt, a preferred DNA substrate for FEN-1 cleavage (48).…”
Section: Discussionmentioning
confidence: 99%
“…Substrates were prepared as described previously (41). Briefly, 10 pmol of the appropriate flap oligonucleotide was 5Ј-radiolabeled with [␥-32 P]ATP and T4 polynucleotide kinase (New England Biolabs) using the manufacturer's protocol.…”
Section: Wrn-exo-1 Coimmunoprecipitationmentioning
confidence: 99%
“…However, it has been shown that PCNA can stimulate Fen1 activity up to 50-fold under physiological salt conditions (16,18). Kinetic analysis revealed that PCNA enhances Fen1 binding stability, thus increasing the cleavage efficiency (28). To efficiently stimulate Fen1 activity, the PCNA trimer must encircle the DNA and must be located "below" the flap (15).…”
Section: Both the Pcna-binding Motif And The C-terminal Tail Of Humanmentioning
confidence: 99%